2021
DOI: 10.1111/ejss.13098
|View full text |Cite
|
Sign up to set email alerts
|

Saturation effect on the distribution of rill detachment rate

Abstract: Detachment rate in rill erosion is an important indicator of soil erosion speed and serves as the basis for estimation of soil erosion using the process‐oriented model. Rill detachment rates on saturated soil slopes were numerically calculated from the dataset of the rill erosion process. The datasets of sediment concentrations were obtained from laboratory experiments, along saturated soil rills 1, 2, 4 and 8 m under slope gradients of 5°, 10°, 15° and 20° and flow rates of 2, 4 and 8 L min−1, and were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…When the water content of the sandy soil reaches the maximum water-holding capacity, the sandy soil begins to discharge. The cohesive force between soil particles of the saturated soil decreases, then the loosened soil particles are easier to detach by water flow [21]. The soil water content of the slope is nearly saturated under the treatment of covering sand, the hydrologic condition of the slope is favorable for the development of erosion [22,23].…”
Section: Soil Lossmentioning
confidence: 99%
“…When the water content of the sandy soil reaches the maximum water-holding capacity, the sandy soil begins to discharge. The cohesive force between soil particles of the saturated soil decreases, then the loosened soil particles are easier to detach by water flow [21]. The soil water content of the slope is nearly saturated under the treatment of covering sand, the hydrologic condition of the slope is favorable for the development of erosion [22,23].…”
Section: Soil Lossmentioning
confidence: 99%
“…Subsequently, the analytical RDRs on saturated loess soil slopes could be computed using the rill length (Equation ( 4)) and sediment concentration (Equation ( 6)). Meanwhile, the RDRs calculated using the numerical method on saturated loess soil slopes were investigated in Huang et al [6] (Table 2).…”
Section: Basic Datasetmentioning
confidence: 99%
“…Shen et al [26] also observed similar relationships with a 4 m flume (the width of 0.1 m) under different hydraulic conditions. Meanwhile, studies also found that RDRs linearly decreased with sediment load on different underlying surfaces or when using different measurement methods [6,[27][28][29]. In addition, Chen et al [30] found that RDRs of a partially thawed soil slope had piecewise functions with rill length, initially maintaining a constant value before exponentially decreasing with rill length.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation